Analisis Kapasitas Ruang Parkir Pasar Soponyono Kota Surabaya - YURIZA FAUZIAH SEMBIRING (Pascasarjana Teknik Sipil Institut Teknologi Nasional Malang, 2024)
This study examines the parking problem at Soponyono Market, a traditional market in Surabaya with a land area of 5000 m2 and a building area of 3500 m2. From the survey results, the off-street parking lot of Soponyono Market is unable to accommodate the surge of vehicles of market visitors during peak market hours. The use of parking lots is not optimal and less organized, resulting in visitors parking vehicles along the road and creating traffic disturbances. Through patrol and inventory survey methods, this study aims to analyze the characteristics, capacity, and parking demand of Soponyono Market. The results showed that the maximum accumulation occurred on Sunday, November 19, 2023 with 573 motorcycles and 90 cars, and a significant spike at 07.01-08.00 WIB. The maximum motorcycle parking volume occurred on Sunday, November 19, 2023, with the highest motorcycle volume reaching 539 vehicles, while cars reached 51 vehicles. The longest parking duration for motorcycles is Tuesday, November 14, 2023 (233 minutes), and for cars is Sunday, November 19, 2023 (299 minutes). The maximum parking turnover rate occurred on Sunday, November 19, 2023 with 2.8 Kend/day/space for motorcycles, and 2.31 Kend/day/space for cars. The maximum parking index for motorcycles and cars is 113% and exceeds 100% respectively. The current parking space capacity is insufficient, so Soponyono Market requires additional parking space of 301.5 m2 for motorcycles and 285.4 m2 for cars. In conclusion, the current condition of parking spaces exceeds the existing capacity, the need for revamping and organizing parking spaces to improve visitor comfort and overcome traffic disturbances around the market.